A review study on axial compression properties of UHPC columns confined by FRP - Song, Shuaiqi; Zhang, Bowen; You, Peibo; Yang, Xiaolong (Frontiers in Materials, 2024)
The failure of ultra-high performance concrete (UHPC) under axial compression has significant brittleness, so it is necessary to use fiber reinforced polymer (FRP) to constrain UHPC for achieving ductile failure. This article mainly summarized the research progress of FRP constrained UHPC columns, analyzed the influence of different variables on the compressive performance of FRP-confined UHPC columns and the coupling effect between variables, compared the axial compressive stress-strain models of FRP-confined UHPC columns proposed by previous scholars, and evaluated the existing models using a large amount of collected experimental data. The evaluation results indicated that the existing models provided relatively accurate predictions for ultimate stress, but further improvement and correction are needed for predicting ultimate strain. Based on the data collected in this study, the models had been modified, resulting in improved accuracy in predicting both ultimate stress and ultimate strain.